KORELASI KOMUNIKASI ORANGTUA/GURU DAN PENINGKATAN DISIPLIN BELAJAR DENGAN PRESTASI BELAJAR SISWA DI SEKOLAH SMK SWASTA TELADAN TANAH JAWA - Sotarduga Sihombing (Nusantara Hasana Berdikari, 2021)
This study aims to determine whether there is a positive and meaningful correlation between parental, teacher communication and increased learning discipline with student achievement in SMK Swasta Teladan Tanah Jawa. This type of research is descriptive quantitative research with the research population is all students of class XI SMK Swasta Teladan Tanah Jawa totaling 293 people. And the sample of this study was 75 people. Data collection techniques used are questionnaires and tests. Based on the results of data analysis, it can be concluded that the multiple correlation coefficient of parental communication with learning achievement is 0.37 and after consulting with the r table (0.05) is 0.334 and the correlation between teacher communication variables and learning achievement is 0.35 and after consultation with rtable (0.05 ) is 0.334, the magnitude of the correlation between the variables of learning discipline and learning achievement is 0.34 and after consulting with rtable (0.05) is 0.334. This means that the hypothesis (Ha) is accepted and it can be concluded that the higher the communication between parents and teachers, the higher the learning achievement. The magnitude of the multiple correlation was found to be 0.28 from the coefficient of determination (R2) of 0.079 which means 7.94% of the variation in Y scores can be explained jointly by the independent variables X1 and X2 and X3. Multiple regression equation: and after being tested with the F statistic, it turned out to be meaningful at the 5% significance level. Thus, it can be concluded that the higher the parental communication, teacher communication and learning discipline, the higher learning achievement.